Gastronomy Tourism in Several Neighbor Countries of Indonesia: a Brief Review - Kurniasih Sukenti (Journal of Indonesian Tourism and Development Studies, 2014)
Gastronomy tourism, also called culinary tourism or food tourism, is a kind of tourism that provide attractions based on the culinary aspect owned by a country, region, or area. It is not only offers food and beverages as the main objects in its attractions, but also everything related to food activities ranging from food ingredients, preparation, processing, serving, as well as the cultural and local values. A well-managed culinary tourism will be a supportive program in developing and enhancing the tourism sector in a country. The objective of this paper is to describe the profile of gastronomy tourism in several neighbor countries of Indonesia, i.e. Hongkong, Singapore, Thailand, and Malaysia. This brief review is also discussed the potential of Indonesia gastronomy in supporting government’s tourism program. Basically, Indonesia has more enormous potential asset in managing its cultural heritages in term of culinary than its neighbor countries. A well-managed gastronomy tourism plays not only an important role in enhancing the economic sector, but also contribute in preserving the natural and cultural resources. Keywords: gastronomy tourism, culinary tourism, food tourism.